A Psychometric Framework for the Evaluation of Instructional Sensitivity. Issue 2 (2nd April 2016) - Naumann, Alexander; Hochweber, Jan; Klieme, Eckhard
Abstract : Although there is a common understanding of instructional sensitivity, it lacks a common operationalization. Various approaches have been proposed, some focusing on item responses, others on test scores. As approaches often do not produce consistent results, previous research has created the impression that approaches to instructional sensitivity are noticeably fragmented. To counter this impression, we present an item response theory–based framework that can help us to understand similarities and differences between existing approaches. Using empirical data for illustration, this article identifies three perspectives on instructional sensitivity: One perspective views instructional sensitivity as the capacity to detect differences in students' stages of learning across points of time. A second perspective treats instructional sensitivity as the capacity to detect differences between groups that have received different instruction. For a third perspective, the previous two are combined to consider differences between both time points and groups. We discuss linking sensitivity indices to measures of instruction.